Food values: How they relate to legality - Marchini, Andrea; Polenzani, Bianca; Ceccarelli, Giulia; Mariano, Eleonora; Martino, Gaetano (Frontiers in Sustainable Food Systems, 2023)
Introduction A value is an implicit principle that arises from judgments about everything around people, whereas a value system is a set of values ordered according to personal preferences. In this context, values can be seen as the adherence to an implicit or explicit set of rules, many of which are related to legality. In this study, legality is understood as the willingness of citizens to abide by the existing set of formal laws. A value system can guide consumers' food choices and provide information on their preferences. In this way, the citizens' food value system can influence the decisions of producers and policymakers. Methods The present study investigates the food value system of a sample of young adults using the Best-Worst Scale method. Results Values such as environmental impact rank high in their value system, indicating that adherence to a set of implicit rules and regulations concerning the environment are very important values when choosing food. Discussion Although adherence to a legal system that protects a public good (the environment) is considered an essential value, legality per se is not. This might suggest, on the one hand, a lack of awareness of legality issues in the Italian food system and, on the other hand, a strong interest in issues perceived as more urgent.